A combined effect of adsorption and reduction potential of biochar derived from Mentha plant waste on removal of methylene blue dye from aqueous solution. Issue 5 (23rd March 2020) - Rawat, Abhay Prakash; Kumar, Vinay; Singh, Devendra Pratap
ABSTRACT: Plant biochars were prepared by slow pyrolysis of Mentha plant waste to remove cationic dye methylene blue (MB) from aqueous solution. The biochars were characterized by X-Ray diffraction, IR-spectroscopy, thermogravimetric analysis, scanning electron microscope, cyclic voltammetry (CV), Brunauer-Emmett-Teller analysis, and zeta potential analyzer. Adsorption isotherms and kinetics applied on the MB dye removal by biochars showed monolayer chemisorption of MB dye. Present investigation revealed that removal of MB dye was due to synergistic action of chemisorption coupled with reductive electron transfer mechanisms. CV test showed a reversible, coupled redox reaction at interface of MB dye and biochar particles.